From Diamond International to Plum Creek: The Era of Large Landscape Conservation in the Northern Forest - Clark, Sara; Howell, Peter (Maine Policy Review, 2007)
The last two decades have seen dramatic, unprecedented growth in conservation lands in the Northern Forest, stretching from upstate New York through Maine. The conservation community, in coordination with public agencies, has been able to take advantage of changing forest ownership structure and a significant expansion of public and private funding to support this increase in protected lands. As Sara Clark and Peter Howell discuss, Maine has been a laboratory for some of the largest and most innovative land transactions. Maine is unique in having land conservation strategies focused almost entirely on permanent protection of privately owned land rather than any significant increase in public ownership, and has served as a testing ground for innovative market-based conservation tools.